Multi‐level bus voltage compensation of droop control with enhanced load‐sharing capability for DC microgrid. Issue 16 (18th December 2018) - Liu, Sucheng; Li, Zhongpeng; Liu, Wenjie; Liu, Xiaodong
Abstract : In DC microgrid, droop control is an essential part of local primary level in hierarchical control to perform load‐sharing and plug‐and‐play function. The main problem with droop control is that better load sharing is achieved at the cost of higher bus voltage drop, which could even be worse when cable resistance is considered. To solve this problem, a multi‐level bus voltage compensation of droop control (MLBVC‐DC) for DC microgrid with enhanced load‐sharing capability is proposed. With high enough droop gain to ensure load‐sharing accuracy, the produced bus voltage drop will be compensated with multi‐level feedforward to the reference bus voltage of DC microgrid according to different load regions. Also, the problem with the piecewise droop at load current setting points is solved by hysteretic control and Control Area Network (CAN) communication. Simulation and experimental results verify the proposed MLBVC‐DC strategy.